2017
DOI: 10.1111/cas.13191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hypoxic microenvironment after radiofrequency ablation on residual hepatocellular cell migration and invasion

Abstract: Clinical observations have shown that the boundary of tumor ablation is often less than safe border and that the use of radiofrequency ablation (RFA) in the treatment of hepatocellular carcinoma (HCC) may probably accelerate its recurrence and metastasis. RFA can cause the formation of a transition zone between normal liver tissues and necrotic coagulation, where blood stagnation and thrombosis expose residual cancer cells to a hypoxic microenvironment. As the blocked vessels are slowly reperfused, the oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 39 publications
(69 reference statements)
2
43
0
Order By: Relevance
“…CD133 is a recognized surface marker for LCSCs [ 15 ]. The mRNA and protein expression levels of CD133 in the iRFA-liver cancer samples were higher than those in the hepatectomy-liver cancer sample (Figures 1(a) – 1(c) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD133 is a recognized surface marker for LCSCs [ 15 ]. The mRNA and protein expression levels of CD133 in the iRFA-liver cancer samples were higher than those in the hepatectomy-liver cancer sample (Figures 1(a) – 1(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…Sublethal heat treatment promotes liver cancer cell development of a spindle-like morphology and transformation CD133-positive liver cancer cells, which are progenitor-like cancer cells that are highly proliferative [ 4 ]. Tong et al have asserted that residual liver cancer cells show a higher percentage of stem-like cells and have levels of invasiveness, metastasis, and drug resistance [ 15 ]. In addition, Wang et al have reported that downregulating the expression of CD133 suppressed proliferation, invasion, and autophagy in iRFA-treated liver cancer [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α has been implicated in regulating hepatic in ammatory progression, and associated with multiple in ammationrelated cancers or signaling pathway activation of HBV-related HCC [20,21] . The presence of hypoxia in tissues restricts HCC overgrowth because of HIF-1α regulating cellular metabolism, immune escape, angiogenesis, metastasis [22] , extracellular matrix remodeling, cancer stem cells (CSC) [23,24] or MDR via regulating PI3K/AKT/HIF-1α/MDR-1 pathway [25,26] . HIF-1α-de cient HCC cells displayed signi cantly reduced anchorage-independent growth and enhanced sensitivity toward chemotherapy [4] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RFA may induce cellular stress and pathological changes in HCC cells. 33 , 34 Several studies suggested that the elevated EMT may account for post-RFA recurrence. 33 – 35 Therefore, inhibiting the EMT process during RFA treatment may be a useful strategy to overcome the recurrence of HCC after RFA treatment.…”
Section: Discussionmentioning
confidence: 99%